(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The properties of the serum composition are analyzed.The methods of adding the necessary components to the composition of serobitum and obtaining high-strength serobitum on their basis have been determined.The methods of analyzing the obtained components have been studied. Methods of obtaining serobitum have been studied. The physico-mechanical properties of serobitum were analyzed. The mechanism of action of additives added to the composition of serobitum has been studied.